Hubungan Asupan Cairan dan Status Hidrasi pada Pekerja: Literature Review - Fedora Micheala Thom; Siti Rahayu Nadhiroh (Universitas Airlangga, 2023)
Background: Dehydration is a condition of lack of fluids in the body because the amount of fluid that comes out is greater than the amount that goes in. Workers are people at risk of dehydration due to insufficient fluid replacement because fluid intake does not meet needs and there is an increase in fluid expenditure. Ensuring workers are adequately hydrated is one way to improve workplace safety and productivity. Objectives: Determine the relationship between fluid intake and hydration status in workers. Methods: This study used literature review method. The literature study was conducted by choosing a cross-sectional design. This study using a electronic databases search strategy from international and national journals. Discussion: There was a significant relationship between fluid intake and workers' hydration status. The majority of workers are dehydrated due to low fluid intake. Conclusions: The conclusion is that fluid intake affects hydration status, but there are several factors such as ambient conditions and type of liquid.